Maximizing Firm Value: The Crucial Roles of Tax Planning, Sales Growth, and Dividend Decisions in Indonesia - Triwibowo, Edi; Sulistyorini Wulandari, Dian; Karningsih, Indah (Journal of International Multidisciplinary Research, 2024)
This study aims to analyze the influence of Tax Planning, Sales Growth, and Dividend Policy on Firm Value in the consumer goods manufacturing sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The independent variables analyzed include Tax Planning, Sales Growth, and Dividend Policy, while the dependent variable is Firm Value. This research utilizes secondary data from financial statements, with sample selection using purposive sampling techniques, resulting in 65 observations from 13 companies that meet the established criteria. The analysis is conducted using multiple linear regression methods. The results indicate that Tax Planning has a negative and significant effect on Firm Value, while Sales Growth does not show a significant effect. On the other hand, Dividend Policy has been proven to have a positive and significant influence on Firm Value. These findings provide valuable insights for management and stakeholders in formulating corporate strategies to enhance firm value through more effective tax and dividend policies.